Understanding Cooperation in an Intertemporal Context - Kölle, Felix; Lauer, Thomas (Management Science, 2024)
Cooperation between individuals, a critical component of organizational and societal success, typically involves costs and benefits that accrue at different points in time. Using a series of controlled experiments, this paper provides a comprehensive analysis of the determinants of cooperation in an intertemporal context. Our findings demonstrate that cooperation is significantly reduced when the benefits of cooperation are shifted into the future, whereas delaying costs leads to an increase in cooperation. Our analysis of the underlying behavioral mechanisms reveals that the change in the level of cooperation can be explained by three factors: (i) a shift in the beliefs about others’ efforts, (ii) a shift in the willingness to conditionally cooperate, and (iii) an individual’s degree of impatience. We further find that injunctive norms of cooperation are unaffected by the timing of consequences, indicating that changes in behavior are due to a change in norm compliance rather than the norm itself. Implications for management practices are discussed. This paper was accepted by Yan Chen, behavioral economics and decision analysis. Funding: Financial support from the Center for Social and Economic Behavior at the University of Cologne and the Deutsche Forschungsgemeinschaft (German Research Foundation) under Germany’s Excellence Strategy [Grant EXC 2126/1- 390838866] is gratefully acknowledged. F. Kölle gratefully acknowledges funding by the European Research Council under the European Union’s Horizon 2020 research and innovation program [Grant 7414099]. Supplemental Material: The online appendix and data files are available at https://doi.org/10.1287/mnsc.2020.03757 .